CHALLENGES AND OPPORTUNITIES FOR THE IMPLEMENTATION OF STRATEGIES WITHIN A HIGHER EDUCATION PRIVATE INSTITUTION IN MATO GROSSO: A CASE STUDY (INMR - Innovation & Management Review, 2008)
This study aims to find out, in the Balanced Scorecard (BSC), some properties for its utilization as a management support tool in a private higher education institution in the state of Mato Grosso. The type of research adopted was the exploratory-descriptive. For the investigation of the present research, the employed approach was the case study. The development of the BSC methodology was split in 5 stages. The first one presented the management tools, mainly with the use of data obtained through primary sources. Following this, there was a description of the requirements for the utilization of the BSC. The third stage defined the development of the BSC methodology. In the fourth stage, the objectives of the institution were detailed. Last but not least, the fifth stage presented the strategic map. Based on data analysis, there was also a dimensioning of the current status of the institution management. The results show that the surveyed individuals have a partial knowledge about the BSC methodology, since not all aspects that make up its concepts have been put into practice by most of them, although they are regarded as important ones.